Entecavir Interacts with Influx Transporters hOAT1, hCNT2, hCNT3, but Not with hOCT2: The Potential for Renal Transporter-Mediated Cytotoxicity and Drug–Drug Interactions - Mandíková, Jana; Volková, Marie; Pávek, Petr; Navrátilová, Lucie; Hyršová, Lucie; Janeba, Zlatko; Pavlík, Jan; Bárta, Pavel; Trejtnar, František (Frontiers in Pharmacology, 2016)
Entecavir (ETV) is one of the most potent agents for the treatment of the hepatitis B viral infection. The drug is principally eliminated by the kidney. The goal of this study was to investigate the potential of ETV to interact in vitro with the renal SLC transporters hOAT1, hOCT2, hCNT2 and hCNT3. Potential drug-drug interactions of ETV at the renal transporters with antiviral drugs known to be excreted by the kidney (adefovir, tenofovir, cidofovir) as well as transporter-dependent cytotoxicity were also examined. Interactions with the selected transporters along with cytotoxicity were studied in several transiently-transfected cellular models using specific substrates and inhibitors. ETV was found to be both a substrate and inhibitor of hOAT1 (IC50 = 175.3 µM), hCNT2 (IC50 = 241.9 µM) and hCNT3 (IC50 = 278.4 µM) transporters, although it interacted with the transporters with relatively low affinities. ETV inhibited the cellular uptake of adefovir, tenofovir and cidofovir by hOAT1; however, effective inhibition was shown at ETV concentrations exceeding therapeutic levels. In comparison with adefovir, tenofovir and cidofovir, ETV displayed no transporter-mediated cytotoxicity in cells transfected with hOAT1, hCNT2, and hCNT3. No significant interaction of ETV with hOCT2 was detected. The study demonstrates interactions of ETV with several human renal transporters. For the first time, an interaction of ETV with the hCNTs was proved. We show that the potency of ETV to cause nephrotoxicity and/or clinically significant drug-drug interactions related to the tested transporters is considerably lower than that of adefovir, tenofovir and cidofovir.